Heavy Metal Removal from Aqueous Solution Using Biosurfactants Produced by Pseudomonas aeruginosa with Corn Oil as Substrate - Venty Suryanti; Sri Hastuti; Tutik Dwi Wahyuningsih; Mudasir Mudasir; Dian Kresnadipayana; Inge Wiratna (Indonesian Journal of Chemistry, 2018)
The batch removal of Cu(II), Cd(II) and Pb(II) from individual heavy metal ion aqueous synthetic solution using biosurfactants produced by Pseudomonas aeruginosa with corn oil as substrate was investigated. The metal ion removal process of crude preparation biosurfactants (CPB) was established to be dependent on the initial pH and contact time. The optimum metal removal was observed at pH 6.0 of the initial metal solution and 10 min of contact time. The affinity sequence for metal ion removal was Pb(II)>Cd(II)>Cu(II). The removal capacity value of biosurfactant for Cu(II), Cd(II) and Pb(II) from single metal ions solution were 0.169, 0.276 and 0.323 mg/g, respectively. The removal capacity value of biosurfactant for Cu(II), Cd(II) and Pb(II) from multi metal ions solution were 0.064, 0.215 and 0.275 mg/g, respectively. The removal capacity of individual metal ion was diminished by the presence of other metal ions in multi metal ions from synthetic aqueous solution. The removal capacity value of biosurfactant for Cu(II), Cd(II) and Pb(II) from silver industry wastewater were 0.027, 0.055 and 0.291 mg/g, respectively. The results indicated that biosurfactants have potential to be used in the remediation of heavy metals in industrial wastewater.